Phytochemical compounds and antiradical, antimicrobial, and cytotoxic activities of the extracts from Hypericum scabrum L. Flowers - Keser, Serhat; Keser, Fatma; Kaygili, Omer; Tekin, Suat; Demir, Ersin; Turkoglu, Ismail; Kirbag, Sevda (Taylor & Francis Ltd, 2020)
Hypericum scabrum L. has been widely used in traditional medicine for the treatment of many diseases just as the other Hypericum species. In the present study, the antiradical, antimicrobial and cytotoxic activities of water and ethanol extracts of H. scabrum flowers were investigated. Their phytochemical contents and composition were also determined. The water and ethanol extracts are better scavenged ABTS (97.89 and 98.99%) and OH radicals (96.36 and 97.33%); the water extract is better scavenged DPPH radicals (91.66%) than the standard antioxidant BHA (94.33, 85.19, 90.16%, respectively). Flowers of H. scabrum contain flavonoids, phenolic acids, vitamins and phytosterols, dominated by catechin, vanillic acid, vitamin K and ergosterol. The extracts exhibit a strong cytotoxic activity against MCF-7, HCT-116, and LNCaP cancer cell lines. It is found that their antimicrobial activities are higher than the standard antibiotics. These results indicate that H. scabrum flowers have potent antiradical, antimicrobial and cytotoxic activities.
Keywords: H; scabrum; antiradical; phytochemical; cytotoxic; antimicrobial